Projeto de dispositivo para encolher pistões de embreagem de câmbios automáticos automotivos - Kaiser, Ismael Anildo (2024)
The growing interest in automotive automatic transmission repairs has generated the need for specialized tools. Repair involves complete disassembly, indicating the need for professional intervention in specific cases. A common defect in automotive automatic transmissions is the inefficiency in sealing the clutch applicator piston rings, resulting in difficulties in starting and changing gears. The challenge of this work lies in compressing the clutch piston springs, requiring specific tools. The work proposes the design of an innovative tool for shrinking clutch piston spring plates, intended for specialized workshops. The equipment was designed through a structured product development method, covering the planning, conception, design and detailing phases. During this process, the project requirements were established, the shrinker concept was defined, the definitive project was prepared and the details were carried out, respectively. As a result of this work, a three-dimensional (3D) model of the equipment was created, accompanied by an assessment of the product's manufacturing costs, including a comparison with a similar model already on the market. With this, the equipment model was obtained that aims to serve different exchange models, facilitating maintenance and reducing costs associated with this specific task.